y-6=-2(x+2)

Simple and best practice solution for y-6=-2(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-6=-2(x+2) equation:


Simplifying
y + -6 = -2(x + 2)

Reorder the terms:
-6 + y = -2(x + 2)

Reorder the terms:
-6 + y = -2(2 + x)
-6 + y = (2 * -2 + x * -2)
-6 + y = (-4 + -2x)

Solving
-6 + y = -4 + -2x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + y = -4 + 6 + -2x

Combine like terms: -6 + 6 = 0
0 + y = -4 + 6 + -2x
y = -4 + 6 + -2x

Combine like terms: -4 + 6 = 2
y = 2 + -2x

Simplifying
y = 2 + -2x

See similar equations:

| (X-10)-4=12 | | 1.1y-(y-0.6)+0.3=0 | | 3x+3(x+5)=30 | | 3-5(4x+5)=78 | | 4(-3+1)=-10(x-4)-14 | | 4x^2-98+180=0 | | 4-7(1-2r)=15.5 | | -29-x=-7x+67 | | 7(x-3)=-3x+89 | | -7+3x-2x=17 | | 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= | | 2(7x-13)=16 | | 5x+(x+2)-3(x-4)=35 | | 5x+3+3x=83 | | 2(7x+13)=16 |

Equations solver categories